Implementing built environment research findings in developing countries - the case of east and Southern Africa the evaluation of implementing industrialized building system for construction industry in Malaysia - Ismail, Zulkefle; Abdul Rahim, Asiah (2009)
The main objectives of this paper are to investigate the significant factors of the implementation of Industrialized Building System (IBS), and the relationship between quality, cost and productivity. The preliminary idea to this research come from the national aspiration of Vision 2020 that is to transform and industrialized the Malaysian construction industry. A system architecture, which takes advantage of new technology, could change the entire construction industry. Most of housing industry in developing countries did not take the advantage of advancement in manufacturing industry especially the implementation of IBS. Factory manufactured components are easy to assembled on-site, use less labour, faster to construct and if has a high quality which will add value to the houses. The methodology used in this study are questionnaire, semi-structured interviews and observation. They are used to identify the status of implementation of IBS in Malaysia. The findings identified that architects and engineers tend to reject the implementation of IBS in Malaysia. The needs to cut cost and improvement in quality of prefabricated components will give a greater drive to its usage in construction sites and achieved customer's satisfaction. The implementation of IBS could help to reduce construction time and site labour. It will also relieve the labour crisis, improved quality while keeping cost reasonable. Further development in prefabrication will also leads to closer integration between building services and manufacturing engineering without compromising the users preference. As a conclusion, to achieve the customer's needs and satisfaction, design guidelines need to be developing as a standard for construction practice in order to enhance the usage of IBS in Malaysia. The Malaysia government should play a greater role in exposing and encouraging the construction industry and the public to the n a. generation of prefabricated components design and technology.